Political Participation of Deaf with Disabilities: A Case Study of Gerkatin Tasikmalaya City in the 2024 Local Election - Olpi Tiani Tamala; Riska Sarofah; Hendra Gunawan (Journal of Political and Governance Studies, 2025)
Background This study examines the political participation of deaf persons with disabilities in Tasikmalaya City during the 2024 Local Election. It aims to understand their forms of participation, levels of involvement, and the barriers they face through the Gerkatin organization as a platform for collective action and advocacy. Methods The research used a qualitative case study approach. This research uses primary data derived from interviews collected directly by researchers or parties requiring data through field collection techniques. Secondary data is obtained from previous research or other sources such as books, journals, and other references related to the research topic. Data validation applied source and technical triangulation. Results The findings show that most Gerkatin members participated through conventional forms, such as voting and limited political discussions. However, their participation was constrained by communication barriers and a lack of disability-friendly political spaces. Despite these challenges, Gerkatin has played a significant role in motivating its members to exercise their voting rights and providing a collective space for self-empowerment. Conclusions Deaf persons with disabilities in Tasikmalaya have participated in 2024 local elections but remain at the observer level of political engagement. Greater accessibility and inclusive political education are needed to enhance their meaningful participation.